Can There be a Feminist Pedagogy within the e-Learning Industrial Complex? - Illuzzi, Michael; Tanjeem, Nafisa (Radical Teacher, 2025)
This article investigates the challenges of pursuing feminist pedagogy within what we call the “e-Learning industrial complex.” It contributes to the existing scholarship on feminist pedagogy, feminist-indigenous-decolonial community engagement, and e-Learning during COVID-19 in several ways. First, it conceptualizes the e-Learning industrial complex and examines how the COVID-19 pandemic has normalized its expansion. It explains how the e-Learning industrial complex appropriates the social justice language of “accessibility” and “affordability” while capitalizing on the urgent demand for e-Learning. In doing so, the e-Learning industrial complex prioritizes e-Learning as a profit-driven venture for neoliberal universities and e-Learning industries, sidestepping both the need for transformative student learning and the imperative to ensure sustainable working conditions for faculty, staff, and other workers. Second, drawing on our experience of pursuing feminist community engagement at Lesley University, this article proposes that the efforts to devise meaningful ways of pursuing feminist pedagogies in digital learning spaces remain incomplete without examining the larger institutional structures, as well as their complicity with the e-Learning industrial complex, against which feminist pedagogies and everyone involved are situated. Third, it argues that the pandemic can turn into a “portal” – as described by Arundhati Roy (2020) – to come out of the chaos. Through collective resistance against the e-Learning industrial complex, students, faculty, staff, and community members can extend the spirit, ethics, and politics of feminist pedagogy outside of the classroom, engage in solidarity with the broader community, and nurture communities of care.